Perception of Patients with Heart Attacks Toward the Warning Signs: A Qualitative Study - Al-zuhairy, Montadhar R; Al- Jubouri, Mohammed Baqer (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To explore patients’ perceptions regarding warning signs of heart attacks.Methods: A descriptive phenomenological design explored 10 perceptions of patients with ischemic heart disease toward warning signs of heart attack by non-probability (purposive) sampling at cardiac care units at Baquba Teaching Hospital and AlKhalis General Hospital For the period from 21st of December, 2023 to 24th of February, 2024.  A 7-item semi-structured interview guide was developed. Qualitative analysis (thematic analysis) was used in the data analysis. This process involved transcribing and translating quotes from Arabic to English for better comprehension. The data analysis procedure consisted of several steps, including first-cycle coding, second-cycle, and analytical notesResults: Six themes and sub-themes emerged. These themes include suspicious recognition, imagination, fear, family roles, experience (experience with heart attack and psychological experience), religious aspects, and repercussions. The themes that emerged included all aspects of the condition that the patient went through during the heart attack from a physical, psychological, and spiritual perspective, which expressed the depths of his sense and cognition.Conclusion: The level of participants' perception is closely linked to their personal experience with heart attack (Whether the sample had heart attack in the present or past). Knowledge alone cannot form perception unless it reaches the individual's psychological aspects, which are shaped through experience.Recommendations: Conducting qualitative research is recommended at a national level and to the whole community to increase the generalizability of the results.